ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP PERSEPSI MAHASISWA TENTANG PENGGUNAAN MOTOR MATIC HONDA - Sari Asih; Agus Fitri Yanto (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2017)
PT Astra Honda Motor (AHM) is a automotive manufacture company in the sport and matic motorcycle. AHM marketing efforts through product, price and advertising appeal. They have creative and attractive advertising to get consumers attention. Pricing also is in conformity with the quality of its products. In this study, primary data used to determine the marketing mix effect against student perceptions about the use of honda matic Motorcycles. The data collection method used the interviews, observations, questionnaires and literature. Then, the authors gave questionnaires to 60 respondents students from Politeknik Sawunggalih Aji and treated using multiple linear regression in SPSS version 20. The analytical results obtained that the marketing mix Influence on students perceptions about product, price and advertising appeal of motorcycles matic Honda. Expressed the value of F count 20.817, with a significance value of 0.000. Product negative effect amounted to - 0.196 against the perception of students. The price (0.621) positive effect on the perception of the students, while the appeal of adverts positive effect of 0.381 on the perception of the students to use matic Honda. For R Square of 0.576, which means that 57.6% variable perception can be explained by product, price and appeal of advertising, while the remaining 42.4% can be explained by other variables that are not used in this study, such as the socio-cultural factors. Keywords: Product, Price and the appeal of advertising Multiple Linear Regression, PolytechnicSawunggalih Aji